1997
DOI: 10.1017/s0022149x00016096
|View full text |Cite
|
Sign up to set email alerts
|

Biosystematics of entomopathogenic nematodes: current status, protocols and definitions

Abstract: COST Action 819: Entomopathogenic nematodes, supercedes Action 812: Cold active lines of insect parasitic nematodes in Agriculture and Biotechnology. It functions in the field of Agriculture and Biotechnology and began in July 1994 and will end in May, 1999. The main objective is to combine interrelated European expertise to increase the use of entomopathogenic nematodes (EPNs) in integrated pest management and to reduce the need for chemical control. Coordination of the Action is the responsibility of a manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
145
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(155 citation statements)
references
References 28 publications
1
145
1
3
Order By: Relevance
“…In the past, morphological traits of males and infective juveniles have been emphasised in the diagnosis and identification of Heterorhabditis species (Stock & Kaya, 1996;Hominick et al, 1997). However, in this study we have shown that most of the 'key' diagnostic features in the Irish Heterorhabditis, were provided by hermaphrodites and females.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In the past, morphological traits of males and infective juveniles have been emphasised in the diagnosis and identification of Heterorhabditis species (Stock & Kaya, 1996;Hominick et al, 1997). However, in this study we have shown that most of the 'key' diagnostic features in the Irish Heterorhabditis, were provided by hermaphrodites and females.…”
Section: Discussionmentioning
confidence: 62%
“…For each of the studied isolates, 20 specimens from each stage (first-generation hermaphrodites, secondgeneration males, second-generation females and third-stage infective juveniles) were randomly collected from 10 G. mellonella cadavers (Hominick et al, 1997). Nematodes were examined live or heatkilled in 60 • C Ringer's solution.…”
Section: Methodsmentioning
confidence: 99%
“…This has stimulated intensive research into all aspects of the biology of these nematodes, and a search for novel genotypes in many countries worldwide. Twenty-three species of Steinernema and 7 of Heterorhabdtitis have been described (Hominick et al 1997(Hominick et al , 1999. The life-cycle of the 2 genera is similar : the infective juvenile, a specialized 3rd-stage juvenile, is the free-living stage and is normally found in soil.…”
Section: Introductionmentioning
confidence: 99%
“…Steinernema also appears to be more species rich than is Heterorhabditis. Twenty two Steinernema species are recognised by Hominick et al (1997). Adams et al (1998) carried out a phylogenetic analysis based on rDNA internal transcribed spacer 1 DNA sequences of nine described species and one putative species of Heterorhabditis and they suggested that three pairs of sister taxa may be conspeci c, thereby delimiting six species of Heterorhabditis.…”
mentioning
confidence: 99%
“…Rapid and reliable diagnostic tests are required for species identication in such surveys and DNA ngerprinting techniques * Corresponding author, e-mail: ann.burnell@may.ie are now becoming more widely used as a rst screen to determine the species composition of newly isolated EPN collections. These molecular approaches can then be supplemented by morphological, morphometric and crossbreeding techniques to con rm the identi cation of putative new species (reviewed by Hominick et al, 1997).…”
mentioning
confidence: 99%